Exploring Archetypal Patterns of the Main Character in Maleficent Movie - Alvina, Anastasia Chika; Rudianto, Gaguk (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2023)
The purpose of the study is to explore the archetypal patterns and how it changes the main character that it gives effect to the movie. Archetypal patterns refer to recurring motifs or fundamental patterns that exist in various cultural expressions, myths, stories, and artworks worldwide. This study used Carl Jung’s theory to identify archetypal patterns. Studying archetypal patterns in film though Jungian theory offers more understanding how symbols are portrayed in the characters, plot, and themes in the movie. The Maleficent movie was used to gather the data. Data collection involved non-participant observation and note-taking technique. In collecting the data. The researchers watched the movie, highlight the parts that related to theory, and then connected to the theory. In analysing the data, the researchers used Miles & Huberman theory which: data reduction, data display, and data conclusion. Maleficent persona can be seen from her interaction with Aurora. Meanwhile, her shadow came out when she felt angry and wanted to revenge.